Phonon Sideband Analysis and Near-Infrared Emission in Heavy Metal Oxide Glasses - Pisarska, Joanna (Materials (Basel), 2020)
In this work, spectroscopic properties of europium and erbium ions in heavy metal oxide glasses have been studied. The phonon energy of the glass host was determined based on Eu(3+) excitation spectra measurements. Near-IR emission spectra at 1550 nm related to (4)I(13/2) → (4)I(15/2) transition of erbium in heavy metal glasses were examined with special regards to luminescence bandwidth and measured lifetime. In particular, correlation between phonon energy and the measured lifetime (4)I(13/2) (Er(3+)) was proposed. The luminescence lifetime for the (4)I(13/2) upper laser state of erbium decreases with increasing phonon energy in glass matrices. Completely different results were obtained glass samples with europium ions, where the (5)D(0) lifetime increases with increasing phonon energy. Our investigations suggest that the values of measured (5)D(0) lifetime equal to radiative lifetimes for all heavy metal oxide glasses.